Integrated optics : devices, materials, and technologies XIII : 26-28 January 2009, San Jose, California, United States - Broquin, Jean-Emmanuel; Greiner, Christoph M. (Christoph Martin), 1968-; SPIE (Society) (Bellingham, Wash. : SPIE)
Includes bibliographical references and author index